Purchasing Behaviour of Polish Consumers in the Internet - Dąbrowska, Anna; Janoś-Kresło, Mirosława (Economic and Environmental Studies, 2020)
In recent years we may observe the growing importance of the Internet in the lives of consumers. As the data from Central Statistical Office (GUS) shows, in 2015 approximately 75.8% of Polish households had access to the Internet. The value of e-commerce is estimated at PLN 27 billion. 54% of Internet users buy in Polish e-shops and 13% in foreign internet shops. The threat of violations of consumer rights, including cybercrime, is on the increase. This requires caution, the knowledge of legislative solutions and litigation methods of exerting consumers’ rights on the part of customers. The article focuses on the purchasing behaviour of Internet users taking into account consumer rights and risks posed by new technologies